Polymer and dispersing agent for reducing viscosity and improving solid content of secondary battery positive electrode slurry and preparation method of polymer and dispersing agent

By using special polymers and dispersants in the preparation of lithium battery positive electrode materials, the environmental protection problem of large amount of NMP solvents is solved, the battery performance and life is improved, the process flow is simplified, and environmental pollution and costs are reduced.

CN119119378APending Publication Date: 2024-12-13WUHAN INSTITUTES OF ADVANCED TECHNOLOGY CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202411233475.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the preparation process of lithium battery positive electrode materials, it is difficult for the prior art to maintain battery performance and electrode quality while reducing the use of NMP solvents, resulting in environmental protection problems and increased equipment costs.

Method used

Using a polymer for reducing viscosity and solid-replenishing and dispersant for secondary battery positive electrode slurry, polypropylene glycol acrylate ester-capped treatment by succinic anhydride, polymerization reaction with styrene, maleic anhydride and acrylic acid was carried out to prepare Polymers with excellent dispersion and wetting effects and mixed with appropriate additives and solvents to form dispersants to reduce the amount of NMP used.

Benefits of technology

This technology effectively reduces the use of NMP, improves the uniformity of the cathode slurry and battery performance, reduces environmental pollution and waste liquid treatment costs, and simplifies the preparation process and improves the life of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005027005210000021
    Figure BDA0005027005210000021
  • Figure BDA0005027005210000061
    Figure BDA0005027005210000061
  • Figure BDA0005027005210000151
    Figure BDA0005027005210000151
Patent Text Reader

Abstract

The invention relates to the technical field of battery materials, in particular to a polymer for reducing viscosity and improving solid content of secondary battery positive electrode slurry, a dispersing agent and a preparation method thereof. The polymer provided by the invention is relatively small in molecular weight, is integrally of a comb-shaped structure, and has excellent dispersion and stability; the polymer contains a benzene ring and a five-membered ring, so that steric hindrance can be formed, the agglomeration of active substances is hindered, and the dispersion stability of slurry is improved; the polymer contains carboxyl, so that the polymer has an excellent anchoring effect; a polyether structure is also contained, so that an excellent wetting effect is achieved; when the dispersing agent is applied to lithium battery positive electrode slurry, viscosity can be reduced, solid content can be improved, then the addition amount of NMP can be reduced, and the problems of environmental pollution caused by addition of a large amount of NMP, cost increase of waste liquid treatment and the like can be well solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery materials, and in particular to a polymer and a dispersant for reducing viscosity and improving solidity of a positive electrode slurry of a secondary battery, and a preparation method thereof. Background Art

[0002] With the development of industry, environmental protection issues have become increasingly prominent, and sustainable development has become the current mainstream direction. In recent years, the battery industry has developed rapidly, and the negative electrode preparation process has tended to be low-toxic and environmentally friendly with water as the solvent. However, in the positive electrode preparation process, especially the positive electrode of power batteries with high performance requirements, due to the material itself and various other reasons, it has not yet been possible to achieve the green and environmentally friendly industrialization mainstream with water as the solvent.

[0003] In recent years, with the surge in the installed capacity of power batteries, the use of N-methylpyrrolidone (NMP), the mainstream solvent used in the preparation of positive electrode slurry, has also increased significantly, and the environmental protection problem of NMP has become increasingly serious. The current mainstream way to solve NMP pollution is condensation collection, but this will greatly increase equipment investment and energy consumption costs. Reducing or not adding NMP solvent can help solve this type of problem, but the existing environmentally friendly solvents are difficult to dissolve binders such as PVDF, and reducing the addition of NMP will cause the viscosity of the positive electrode slurry to increase while causing uneven dispersion of active materials, thereby affecting the quality of the positive electrode sheet and battery performance. Therefore, the current mainstream process of lithium battery positive electrode is still based on NMP solvent. How to reduce the use of NMP solvent without affecting the quality of the electrode sheet and battery performance is a current research hotspot.

[0004] In order to solve the above problems, those skilled in the art have made a series of attempts from the perspective of optimizing polymer dispersants. Among them, styrene-maleic anhydride copolymer (SMA) dispersants have become a research direction, such as CN 113248722A, a styrene-maleic anhydride modified copolymer dispersant and its preparation method. Styrene-maleic anhydride copolymer (SMA) dispersants have been used in the coating industry at home and abroad for many years. After a long period of market testing, its dispersing effect is very excellent and has also been rapidly developed in industries such as construction. However, in the preparation process of lithium battery positive electrode materials, the existing SMA dispersants, due to the large amount of addition that affects the battery performance and energy density, result in the addition amount of dispersants cannot exceed 0.5% of the solid matter, and the SMA dispersant structure itself lacks a wetting effect, and it is difficult to effectively reduce the use of NMP solvent when a small amount of SMA dispersants are added, so the existing SMA dispersants do not solve the above problems well. Summary of the invention

[0005] The embodiments of the present application provide a polymer for reducing viscosity and improving solidity of a secondary battery positive electrode slurry, a dispersant and a preparation method thereof, so as to solve the environmental problem caused by the need to add a large amount of NMP solvent during the preparation of lithium battery positive electrode materials in the related art.

[0006] In the first aspect, a polymer for reducing viscosity and improving solidification of a secondary battery positive electrode slurry is provided, having the following structure:

[0007]

[0008] Among them, a=2~24; b=2~16; c=2~8; d=2~40; n=2~32.

[0009] In a second aspect, a dispersant for reducing viscosity and improving solidity of a secondary battery positive electrode slurry is provided, the components of which include additives, solvent a, solvent b and the above-mentioned polymer.

[0010] In any embodiment, the proportions of the polymer, additive, solvent a and solvent b in the dispersant are 10% to 35%, 20% to 30%, 18% to 25%, and 10% to 52%, respectively.

[0011] In any embodiment, the additive is at least one of isopropanolamine, diisopropanolamine, and triisopropanolamine.

[0012] In any embodiment, the solvent a is at least one of ethanol, propylene glycol, isopropanol, and isobutanol; the solvent b is at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), and N,N-dimethylacetamide (DMAC).

[0013] A third aspect provides a method for preparing a polymer, comprising the following steps:

[0014] Step 1, using succinic anhydride to esterify and end-cap polypropylene glycol acrylate (AA-PPG) to obtain a macromonomer acrylate-succinic acid monoester-poly (propylene glycol) (AA-PPGS);

[0015] Step 2, polymerizing styrene, maleic anhydride (MA), acrylic acid and AA-PPGS to obtain a crude polymer;

[0016] Step 3: purify the crude polymer to obtain a high-purity polymer.

[0017] In any embodiment, the process of the esterification and end-capping treatment in step 1 is:

[0018] Succinic anhydride and AA-PPG are mixed, a catalyst is added, and the mixture is stirred and heated under an inert atmosphere to react. After the reaction is completed, the obtained product is extracted and dried to obtain the AA-PPGS.

[0019] In any embodiment, the molecular weight of the AA-PPG is 200-2000; preferably, the molecular weight is 300-500; more preferably, the molecular weight is 400.

[0020] In any embodiment, the catalyst is at least one of sulfuric acid, hydrochloric acid, formic acid, ferric chloride, and p-toluenesulfonic acid;

[0021] Preferably, the catalyst is p-toluenesulfonic acid.

[0022] In any embodiment, the heating temperature is 60-120°C.

[0023] In any embodiment, the molar ratio of succinic anhydride to AA-PPG is (1.1:1) to (2.5:1).

[0024] In any embodiment, the amount of the catalyst is 0.5 wt% to 2.5 wt% of the total mass of succinic anhydride and AA-PPG.

[0025] In any embodiment, the process of the polymerization reaction is:

[0026] Add the AA-PPGS obtained in step 1 to the organic solvent, then add maleic anhydride and an initiator, heat under inert atmosphere, add a chain transfer agent, and then dropwise add a styrene solution and an acrylic acid solution. After the reaction is completed, evaporate the solvent to obtain the crude polymer.

[0027] Optionally, the initiator can be added once or twice; when the initiator is added twice, the second addition can be performed after the styrene solution and the acrylic acid solution are added dropwise; preferably, the initiator is added twice.

[0028] In any embodiment, the organic solvent is at least one of dimethyl carbonate (DMC), propylene glycol methyl ether (PM), tetrahydrofuran (THF), N,N-dimethylformamide (DMF), and N-methylpyrrolidone (NMP); this type of organic solvent can achieve this reaction.

[0029] Preferably, the organic solvent is PM or NMP.

[0030] In any embodiment, the heating temperature is 60-110°C.

[0031] In any embodiment, the chain transfer agent is at least one of 3-mercaptopropionic acid, mercaptoethanol, thioglycolic acid, sodium methyl propylene sulfonate, and dodecyl mercaptan;

[0032] In any embodiment, the added amount of the chain transfer agent is 3 wt % to 10 wt % of the total mass of AA-PPG and maleic anhydride.

[0033] In any embodiment, the initiator is one of azobisisobutyronitrile (AI BN) and benzoyl peroxide;

[0034] Preferably, the initiator is AI BN.

[0035] In any embodiment, the added amount of the initiator is 2 wt% to 15 wt% of the total mass of AA-PPG and maleic anhydride.

[0036] In any embodiment, the molar ratio of styrene, maleic anhydride, acrylic acid, and AA-PPGS is (1:1:1:1) to (3:2:1:5);

[0037] In any embodiment, the specific process of purification in step 3 is:

[0038] The crude polymer obtained in step 2 is dissolved in acetone, then subjected to extraction and drying treatments, and finally vacuum dried.

[0039] In any embodiment, the vacuum drying temperature is 40-100°C.

[0040] In a fourth aspect, a method for preparing a dispersant is provided, comprising the following steps:

[0041] The additive, solvent a, solvent b and the polymer provided in the first aspect of the present application are mixed evenly to obtain the dispersant.

[0042] The beneficial effects of the technical solution provided by this application include:

[0043] 1. The polymer provided in the embodiment of the present application has a small molecular weight and a comb-like structure as a whole, and has excellent dispersion and stability; the polymer contains a benzene ring and a five-membered ring, which can form a steric hindrance, thereby hindering the agglomeration of active substances and increasing the dispersion stability of the slurry; and the polymer contains a carboxyl group, which has an excellent anchoring effect; and also contains a polyether structure, which has an excellent wetting effect;

[0044] 2. The preparation method of the polymer provided in this application adopts a one-step synthesis process, and does not require post-modification. Compared with the post-modification process, it has the advantages of simple and easy operation, short reaction time, sufficient reaction, high yield, and simple purification;

[0045] 3. The dispersant provided in the embodiment of the present application contains the special polymer of the present application, and can be used in the positive electrode slurry of lithium batteries to reduce viscosity and increase solids, thereby reducing the amount of organic solvent / NMP added, and can better solve the problems of environmental pollution and increased cost of waste liquid treatment caused by the large amount of organic solvent / NMP added;

[0046] 4. The battery positive electrode material provided in the present application uses a specific dispersant, which can increase the uniformity of the positive electrode slurry, improve the yield rate of the positive electrode sheet, and thus increase the life of the lithium-ion battery. DETAILED DESCRIPTION

[0047] The technical solution of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.

[0048] In the first aspect, a polymer for reducing viscosity and improving solidification of a secondary battery positive electrode slurry is provided, having the following structure:

[0049]

[0050] Among them, a=2~24; b=2~16; c=2~8; d=2~40; n=2~32.

[0051] a, b, c, d, and n are selected in the above appropriate range. The value range of a, b, c, d, and n mainly affects the molecular weight of the polymer. When a, b, c, d, and n are too small, the molecular weight of the polymer is too small and the stability is poor, which can easily affect the stability of the battery; when the values ​​of a, b, c, d, and n are too large, the molecular weight is too high, which will lead to poor viscosity reduction effect.

[0052] In a second aspect, a dispersant for reducing viscosity and improving solidity of a secondary battery positive electrode slurry is provided, the components of which include additives, solvent a, solvent b and the above-mentioned polymer.

[0053] In any embodiment, the proportions of the polymer, additive, solvent a and solvent b in the dispersant are 10% to 35%, 20% to 30%, 18% to 25%, and 10% to 52%, respectively.

[0054] In any embodiment, the additive is at least one of isopropanolamine, diisopropanolamine, and triisopropanolamine.

[0055] In any embodiment, the solvent a is at least one of ethanol, propylene glycol, isopropanol, and isobutanol; the solvent b is N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), and N,N-dimethylacetamide (DMAC).

[0056] The addition of two solvents in the present application can better match the polymer dispersed battery slurry provided in the present application, and the use of the above two solvents mixed can provide better viscosity reduction effect and stability.

[0057] A third aspect provides a method for preparing a polymer, comprising the following steps:

[0058] Step 1, using succinic anhydride to esterify and cap polypropylene glycol acrylate (AA-PPG) to obtain a macromonomer acrylate-succinic acid monoester-poly (propylene glycol) (AA-PPGS);

[0059] Step 2, polymerizing styrene, maleic anhydride (MA), acrylic acid and AA-PPGS to obtain a crude polymer;

[0060] Step 3: purify the crude polymer to obtain a high-purity polymer.

[0061] In any embodiment, the process of the esterification and end-capping treatment in step 1 is:

[0062] Succinic anhydride and AA-PPG are mixed, a catalyst is added, and the mixture is stirred and heated under an inert atmosphere to react. After the reaction is completed, the obtained product is extracted and dried to obtain the AA-PPGS.

[0063] In any embodiment, the molecular weight of the AA-PPG is 200-2000; preferably, the molecular weight is 300-500; more preferably, the molecular weight is 400.

[0064] If the molecular weight of AA-PPG is too small, it will affect the wetting effect and stability; if the molecular weight is too large, the chain will be too long and difficult to stretch, which will increase the viscosity of the slurry.

[0065] In any embodiment, the catalyst is at least one of sulfuric acid, hydrochloric acid, formic acid, ferric chloride, and p-toluenesulfonic acid;

[0066] Preferably, the catalyst is p-toluenesulfonic acid; p-toluenesulfonic acid has a higher catalytic activity, can be added in a smaller amount and has the advantages of low toxicity, easy degradation and little pollution.

[0067] In any embodiment, the heating temperature is 60-120°C.

[0068] In any embodiment, the molar ratio of succinic anhydride to AA-PPG is (1.1:1) to (2.5:1).

[0069] In any embodiment, the amount of the catalyst is 0.5 wt% to 2.5 wt% of the total mass of succinic anhydride and AA-PPG.

[0070] In any embodiment, the process of the polymerization reaction is:

[0071] Add the AA-PPGS obtained in step 1 to the organic solvent, then add maleic anhydride and initiator, heat under inert atmosphere, add chain transfer agent, and then dropwise add styrene solution and acrylic acid solution at the same time. After the reaction is completed, evaporate the solvent to obtain a crude polymer.

[0072] Optionally, the initiator can be added once or twice; when the initiator is added twice, the second addition can be performed after the styrene solution and the acrylic acid solution are added dropwise; preferably, the initiator is added twice to better control the reaction.

[0073] In any embodiment, the organic solvent and the solvents used in the styrene solution and the acrylic acid solution are at least one of dimethyl carbonate (DMC), propylene glycol methyl ether (PM), tetrahydrofuran (THF), N,N-dimethylformamide (DMF), and N-methylpyrrolidone (NMP); such organic solvents can achieve the reaction in this step.

[0074] Preferably, the solvent is PM or NMP; such solvents are beneficial to reducing side reactions and have relatively good compatibility with the prepared AA-PPGS, which is more conducive to subsequent purification reactions.

[0075] In any embodiment, after the AA-PPGS obtained in step 1 is added to the organic solvent, the content of AA-PPGS is 15 wt % to 80 wt %.

[0076] In any embodiment, the mass fraction of styrene in the styrene solution is 10 wt % to 70 wt %.

[0077] In any embodiment, the mass fraction of acrylic acid in the acrylic acid solution is 10 wt % to 60 wt %.

[0078] In any embodiment, the heating temperature is 60-110°C.

[0079] In any embodiment, the chain transfer agent is at least one of 3-mercaptopropionic acid, mercaptoethanol, thioglycolic acid, sodium methyl propylene sulfonate, and dodecyl mercaptan;

[0080] In any embodiment, the amount of the chain transfer agent added is 3% to 10% of the total mass of AA-PPG and maleic anhydride;

[0081] If the amount of chain transfer agent added is too small, the molecular weight will be too large, the chain will be too long to stretch, and the wetting effect will be poor; if the amount added is too large, it will lead to incomplete polymerization and the formation of more impurities that are difficult to purify.

[0082] In any embodiment, the initiator is one of azobisisobutyronitrile (AI BN) and benzoyl peroxide;

[0083] Preferably, the initiator is AI BN; AI BN is more environmentally friendly and has fewer side reactions.

[0084] In any embodiment, the added amount of the initiator is 2% to 15% of the total mass of AA-PPG and maleic anhydride.

[0085] In any embodiment, the molar ratio of styrene, maleic anhydride, acrylic acid, and AA-PPGS is (1:1:1:1) to (3:2:1:5);

[0086] In any embodiment, the specific process of purification in step 3 is:

[0087] The crude polymer obtained in step 2 is dissolved in acetone, then subjected to extraction and drying treatments, and finally vacuum dried.

[0088] In any embodiment, the vacuum drying temperature is 40-100°C.

[0089] In a fourth aspect, a method for preparing a dispersant is provided, comprising the following steps:

[0090] The additive, solvent a, solvent b and the polymer provided in the first aspect of the present application are mixed evenly to obtain the dispersant.

[0091] Example 1

[0092] 1. Preparation of polymer

[0093] Step 1, mixing succinic anhydride and AA-PPG (molecular weight 400) at a molar ratio of succinic anhydride to AA-PPG of 1.5:1, adding a catalyst of p-toluenesulfonic acid at a total mass of succinic anhydride and AA-PPG of 1.5wt%, stirring under a N2 atmosphere and heating to 85°C for reaction, after the reaction is completed, dissolving the obtained product in dichloromethane, extracting, and drying to obtain the AA-PPGS;

[0094] Step 2, adding the AA-PPGS obtained in step 1 to NMP until the AA-PPGS content is 50wt%, and then adding maleic anhydride, and adding initiator AI BN according to 8% of the total mass of styrene, maleic anhydride, acrylic acid and AA-PPGS; heating to 85°C under N2 atmosphere, and adding 3-mercaptopropionic acid according to 6% of the total mass of styrene, maleic anhydride, acrylic acid and AA-PPGS, and then simultaneously adding dropwise 50wt% styrene NMP solution and 40wt% acrylic acid NMP solution to react, the molar ratio of the added styrene, maleic anhydride, acrylic acid, and AA-PPGS is 6:4:3:11; after the reaction is completed, evaporating the solvent to obtain a crude polymer;

[0095] Step 3: The crude polymer obtained in step 2 is dissolved in acetone, then precipitated and extracted with ethanol, and finally vacuum dried at 50°C.

[0096] 2. Preparation of dispersant

[0097] The polymer, isopropanolamine, ethanol and NMP are mixed evenly according to the proportions of 15%, 25%, 20% and 40% respectively to obtain the dispersant.

[0098] Example 2

[0099] 1. Preparation of polymer

[0100] Step 1, mixing succinic anhydride and AA-PPG (molecular weight 200) at a molar ratio of succinic anhydride to AA-PPG of 1.1:1, adding concentrated sulfuric acid in an amount of 0.5wt% of the total mass of succinic anhydride and AA-PPG, stirring under a N2 atmosphere and heating to 60°C for reaction, after the reaction is completed, dissolving the obtained product in dichloromethane, extracting, and drying to obtain the AA-PPGS;

[0101] Step 2, adding the AA-PPGS obtained in step 1 to the organic solvent PM until the AA-PPGS content is 25wt%; then adding maleic anhydride, and adding benzoyl peroxide at 3% of the total mass of styrene, maleic anhydride, acrylic acid, and AA-PPGS; heating to 60° C. under nitrogen atmosphere, and adding mercaptoethanol at 8wt% of the total mass of (styrene, maleic anhydride, acrylic acid, AA-PPGS), and at the same time, dripping a 30wt% styrene PM solution and a 25wt% acrylic acid PM solution, the added styrene, maleic anhydride, acrylic acid, AA-PPGS in a molar ratio of 2:1:1:3; after the reaction is completed, evaporating the solvent to obtain a crude polymer;

[0102] Step 3: The crude polymer obtained in step 2 is dissolved in acetone, then precipitated and extracted with ethanol, and finally vacuum dried at 50°C.

[0103] 2. Preparation of dispersant

[0104] The polymer, isopropanolamine, ethanol and NMP are mixed evenly according to the proportions of 35%, 20%, 25% and 20% respectively to obtain the dispersant.

[0105] Example 3

[0106] 1. Preparation of polymer

[0107] Step 1, mixing succinic anhydride and AA-PPG (molecular weight 2000) at a molar ratio of succinic anhydride to AA-PPG of 2.5:1, adding formic acid in an amount of 2.5wt% of the total mass of succinic anhydride and AA-PPG, stirring under a N2 atmosphere and heating to 120°C for reaction, after the reaction is completed, dissolving the obtained product in dichloromethane, extracting, and drying to obtain the AA-PPGS;

[0108] Step 2, adding the AA-PPGS obtained in step 1 to DMF until the content of AA-PPGS is 65wt%; then adding maleic anhydride, and adding AI BN at 11% of the total mass of styrene, maleic anhydride, acrylic acid, and AA-PPGS; heating to 110° C. under nitrogen atmosphere, and adding thioglycolic acid at 3wt% of the total mass of styrene, maleic anhydride, acrylic acid, and AA-PPGS, and at the same time, dripping 70wt% styrene DMF solution and 60wt% acrylic acid DMF solution, the molar ratio of the added styrene, maleic anhydride, acrylic acid, and AA-PPGS is 3:2:1:5; after the reaction is completed, evaporating the solvent to obtain a crude polymer;

[0109] Step 3: The crude polymer obtained in step 2 is dissolved in acetone, then precipitated and extracted with ethanol, and finally vacuum dried at 50°C.

[0110] 2. Preparation of dispersant

[0111] The polymer, isopropanolamine, ethanol and NMP are mixed evenly according to the proportions of the polymer, isopropanolamine, ethanol and NMP respectively being 10%, 30%, 18% and 42% to obtain the dispersant.

[0112] Example 4

[0113] 1. Preparation of polymer

[0114] Step 1, mixing succinic anhydride and AA-PPG (molecular weight of 1000) at a molar ratio of succinic anhydride to AA-PPG of 2:1, adding p-toluenesulfonic acid in an amount of 1wt% of the total mass of succinic anhydride and AA-PPG, stirring under a N2 atmosphere and heating to 90°C for reaction, after the reaction is completed, dissolving the obtained product in dichloromethane, extracting, and drying to obtain the AA-PPGS;

[0115] Step 2, adding the AA-PPGS obtained in step 1 to THF until the AA-PPGS content is 40wt%; then adding maleic anhydride, and adding initiator AI BN according to 5wt% of the total mass of styrene, maleic anhydride, acrylic acid and AA-PPGS; heating to 85°C under inert atmosphere conditions, and adding dodecyl mercaptan according to 5wt% of the total mass of styrene, maleic anhydride, acrylic acid and AA-PPGS, and at the same time, dripping 40wt% styrene THF solution and 40wt% acrylic acid THF solution, the molar ratio of the added styrene, maleic anhydride, acrylic acid and AA-PPGS is 3:1:1:4; after the reaction is completed, evaporating the solvent to obtain a crude polymer;

[0116] Step 3: The crude polymer obtained in step 2 is dissolved in acetone, then precipitated and extracted with ethanol, and finally vacuum dried at 50°C.

[0117] 2. Preparation of dispersant

[0118] The polymer, isopropanolamine, ethanol and NMP are mixed evenly according to the proportions of 35%, 30%, 25% and 15% respectively to obtain the dispersant.

[0119] Comparative Example 1

[0120] 1. Preparation of polymer

[0121] The molecular weight of AA-PPG added in this comparative example is 2500; other characteristics are the same as those in Example 1.

[0122] 2. Preparation of dispersant

[0123] Same as Example 1.

[0124] Comparative Example 2

[0125] Preparation of dispersants

[0126] The polymer, isopropanolamine, ethanol and NMP are mixed evenly according to the proportions of the polymer, isopropanolamine, ethanol and NMP being 15%, 25%, 20% and 40% respectively, to obtain the dispersant.

[0127] The polymer is a polymer prepared by an existing method. The preparation method refers to Example 1 of patent CN 113248722B. The specific process is:

[0128] Preparation of styrene maleic anhydride modified copolymer dispersant K1: (1) Add 120 g of DMF to a 1 L reaction bottle and heat to 80°C, slowly add 80 g of SMA1000P, stir evenly, slowly drop 2.6 g of methanol, and react at 80°C for 2 h;

[0129] (2) At 80°C, a mixture of 12.2 g of 85% hydrazine hydrate and 10 g of DMF was added dropwise to the reaction flask, and the mixture was reacted at 80°C for 3 h;

[0130] (3) Remove unreacted hydrazine hydrate and methanol generated in the reaction under reduced pressure at 120°C, cool to 80°C, slowly dropwise add a mixture of 8.5 g of benzaldehyde, 30 g of DMF and 2 drops of glacial acetic acid into the reaction flask, and react at a constant temperature of 80°C for 3 h; (4) Add 384 g of MPEG1200 into the reaction flask, and carry out esterification reaction at a constant temperature of 140°C for 3 h; (5) Remove the solvent under reduced pressure to obtain a polymer.

[0131] Comparative Example 3

[0132] Preparation of dispersants

[0133] The polymer and NMP are mixed evenly according to 15% of polymer and 85% of NMP to obtain the dispersant.

[0134] The polymer is a polymer prepared by an existing method, and the preparation method is the same as that of Comparative Example 2, and the specific process is as follows:

[0135] Preparation of styrene maleic anhydride modified copolymer dispersant K1: (1) Add 120 g of DMF to a 1 L reaction bottle and heat to 80°C, slowly add 80 g of SMA1000P, stir evenly, slowly drop 2.6 g of methanol, and react at 80°C for 2 h;

[0136] (2) At 80°C, a mixture of 12.2 g of 85% hydrazine hydrate and 10 g of DMF was added dropwise to the reaction flask, and the mixture was reacted at 80°C for 3 h;

[0137] (3) Remove unreacted hydrazine hydrate and methanol generated in the reaction under reduced pressure at 120°C, cool to 80°C, slowly dropwise add a mixture of 8.5 g of benzaldehyde, 30 g of DMF and 2 drops of glacial acetic acid into the reaction flask, and react at a constant temperature of 80°C for 3 h; (4) Add 384 g of MPEG1200 into the reaction flask, and carry out esterification reaction at a constant temperature of 140°C for 3 h; (5) Remove the solvent under reduced pressure to obtain a polymer.

[0138] Comparative Example 4

[0139] Preparation of dispersants

[0140] The polymer, isopropanolamine, ethanol and NMP are mixed evenly according to the proportions of the polymer, isopropanolamine, ethanol and NMP being 15%, 25%, 20% and 40% respectively, to obtain the dispersant.

[0141] The polymer is a polymer prepared by an existing method. The preparation method refers to Example 1 of patent application CN 111333782A. The specific process is as follows:

[0142] 550g of styrene-maleic anhydride copolymer, 13.1g of hydroxyethyl methacrylate and 0.08g of 2,6-di-tert-butyl-p-methylphenol are added to 550g of a dibasic acid ester solvent, the reaction temperature is maintained at 80°C to 130°C, and the acid value change in the system is monitored. When the acid value is 50% to 55% of the initial acid value, 0.08g of triphenylphosphine and 8.5g of glycidyl methacrylate are added to continue the reaction. When the acid value in the system is 45mgKOH / g to 50mgKOH / g, the reaction is stopped to obtain the polymer.

[0143] Performance Testing

[0144] The dispersant, NMP solvent, lithium iron phosphate, PVDF binder, and conductive carbon black SP prepared in the examples and comparative examples were mixed according to the laboratory test formula to obtain a positive electrode slurry, which was then tested. The addition amount of each substance is shown in Table 1:

[0145] A control group is set up. The difference between the preparation method of the positive electrode slurry of the button-type lithium battery in the control group and the preparation method of the positive electrode slurry of the button-type lithium battery is that no dispersant is added. Then, the performance test is carried out using the same test method as the embodiment and the comparative example.

[0146] Table 1

[0147]

[0148]

[0149] Test 1:

[0150] The positive electrode slurry viscosity test was performed on the embodiments, comparative examples and control group according to Table 1. The dispersion stability can be compared by comparing the discharge viscosity and the 1h viscosity. The test results are shown in Table 2.

[0151] Table 2

[0152] Discharge viscosity (cp) 1h viscosity (cp) Control group 8300(12# rotor 30rpm) 10530(12# rotor 30rpm) Example 1 4900(12# rotor 30rpm) 5010(12# rotor 30rpm) Example 2 6430(12# rotor 30rpm) 7980(12# rotor 30rpm) Example 3 7780(12# rotor 30rpm) 8610(12# rotor 30rpm) Example 4 6750(12# rotor 30rpm) 7030(12# rotor 30rpm) Comparative Example 1 6450(12# rotor 30rpm) 6570(12# rotor 30rpm) Comparative Example 2 6390(12# rotor 30rpm) 7720(12# rotor 30rpm) Comparative Example 3 7750(12# rotor 30rpm) 8540(12# rotor 30rpm) Comparative Example 4 6270(12# rotor 30rpm) 6650(12# rotor 30rpm)

[0153] Test 2:

[0154] The solid content improvement of the embodiment, comparative example and control group at the approximate slurry viscosity was tested. Taking the viscosity of the control group at 55% solid content as the standard, NMP was gradually added until the viscosity was close to the standard, and then about 1g of slurry was taken for solid content testing. The test results are shown in Table 3.

[0155] Table 3

[0156] LFP SP PVDF glue (5wt%) NMP Dispersants Measured solid content Control group 24g 0.5g 10g 10.96g / 55.0% Example 1 24g 0.5g 10g 3.68g 0.5g 64.6% Example 2 24g 0.5g 10g 5.53g 0.21g 62.1% Example 3 24g 0.5g 10g 8.36g 0.75g 57.3% Example 4 24g 0.5g 10g 6.65g 0.21g 60.5% Comparative Example 1 24g 0.5g 10g 5.69g 0.5g 61.4% Comparative Example 2 24g 0.5g 10g 6.15g 0.5g 60.7% Comparative Example 3 24g 0.5g 10g 9.12g 0.5g 56.8% Comparative Example 4 24g 0.5g 10g 5.41g 0.5g 61.9%

[0157] It can be seen from the above table that the dispersant containing a specific polymer provided in the present application has a good dispersing effect, can increase the solid content of the positive electrode slurry during the processing, and is used to prepare the positive electrode slurry of the secondary battery, which is beneficial to reduce the amount of organic solvents such as NMP added, which is beneficial to environmental protection; while in the comparative example or the control group, the molecular weight of the prepared polymer is not suitable (Comparative Example 1), which will result in poor viscosity reduction and solidification effect on the positive electrode slurry, or the dispersant prepared by the existing polymer (Comparative Examples 2 and 4) does not have good wetting properties, has limited improvement in the dispersion effect, and cannot improve the solid content well, or compared with the existing method (Comparative Example 3), the viscosity reduction and solidification effect on the positive electrode slurry is limited.

[0158] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A polymer for reducing viscosity and improving solidification of secondary battery positive electrode slurry, characterized in that: It has the following structure: Among them, a=2~24; b=2~16; c=2~8; d=2~40; n=2~32.

2. A dispersant for reducing viscosity and improving solidification of secondary battery positive electrode slurry, characterized in that: The components thereof include additives, solvent a, solvent b and the polymer according to claim 1.

3. The dispersant according to claim 2, characterized in that The mass proportions of the polymer, additive, solvent a and solvent b in the dispersant are 10% to 35%, 20% to 30%, 18% to 25% and 10% to 52% respectively.

4. The dispersant according to claim 2, characterized in that The additive is at least one of isopropanolamine, diisopropanolamine and triisopropanolamine.

5. The dispersant according to claim 2, characterized in that The solvent a is at least one of ethanol, propylene glycol, isopropanol and isobutanol.

6. The dispersant according to claim 2, characterized in that The solvent b is at least one of N-methylpyrrolidone, N,N-dimethylformamide and N,N-dimethylacetamide.

7. A method for preparing the polymer according to claim 1, characterized in that: The following steps are involved: Step 1, using succinic anhydride to esterify and cap polypropylene glycol acrylate (AA-PPG) to obtain a macromonomer acrylate-succinic acid monoester-poly (propylene glycol) (AA-PPGS); Step 2, polymerizing styrene, maleic anhydride, acrylic acid and AA-PPGS to obtain a crude polymer; Step 3: purify the crude polymer to obtain a high-purity polymer.

8. The method for preparing a polymer according to claim 7, characterized in that: The process of esterification and end-capping treatment in step 1 is: Succinic anhydride and AA-PPG are mixed, a catalyst is added, and the mixture is stirred and heated under an inert atmosphere to react. After the reaction is completed, the obtained product is extracted and dried to obtain the AA-PPGS.

9. The method for preparing a polymer according to claim 7, characterized in that: The process of the polymerization reaction is: Add the AA-PPGS obtained in step 1 to the organic solvent, then add maleic anhydride and an initiator, heat under inert atmosphere, add a chain transfer agent, and then dropwise add a styrene solution and an acrylic acid solution. After the reaction is completed, evaporate the solvent to obtain the crude polymer.

10. A method for preparing a dispersant, characterized in that: The method comprises the following steps: taking an additive, a solvent a, a solvent b and the polymer described in claim 1 and mixing them uniformly to obtain the dispersant.

Citation Information

Patent Citations

  • Modified styrene-maleic anhydride resin, and preparation method and application thereof

    CN111333782A

  • Novel styrene-maleic anhydride modified copolymer dispersant and preparation method thereof

    CN113248722A

  • A styrene-maleic anhydride modified copolymer dispersant and its preparation method

    CN113248722B

Cited By

  • Method for improving stability of sodium ion battery polyanion positive electrode slurry

    CN120600810A